(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This article discusses issues of social protection for older people. As well as a number of principles that, if implemented, should help older people lead full-blooded and fruitful lives. These principles are grouped into five groups: independence, participation, care, realization of inner potential, dignity. The problems of aging and old age are explored. Here, aging is seen as a process, and old age is understood as its result.